A Study A Study of Female Suffered from HIV Wasting Syndrome and Pulmonary Tuberculosis - Rachmatullah, Tri Ferry (Sultan Agung Islamic University of Semarang, 2023)
Background: Tuberculosis is the most often secondary infection of people living with HIV / AIDS. The tuberculosis co- infection with HIV will increase the risk of death. The purpose of this study was to understand the management of patient with HIV wasting syndrome and tuberculosis. Methods : A 45 years old female with HIV AIDS which being treated with ARV for 6 months, admitted to hospital with general weakness which was continuously progressive in three weeks. She felt fatigue and only lying on her bed for almost 2 month after she was hospitalized because of CNS infection. Sometimes there were fever, mild cough and vomitting. The general condition was weak, body mass index was 14.4 kg/m2 (underweight) and she got a nasogastrictube. Result: The laboratory finding showed anaemia ( 8,1 g/dl), hypokalemia (2,4 mmol/L), hypoproteinemia (4,9 g/dl), hypoalbuminemia (2,1 g/dl) and elevated of liver function test (AST 61 U/L, ALP 155 U/L), GGT 206 U/L). CD 4 count 34 cells / mm3 (410-1590 cells / mm3) and viral load detected 694.648 copies / ml. The chest X ray showed some infiltrate due to tuberculosis that has been diagnosed and treated earlier. Patientwere treated with anti retro viral, anti tuberculosis, red cell transfusion, albumin transfusion, physiotherapy, occupational therapy and adequate nutritional management. The condition of the patient was getting better on several follow up and she was permitted to discharged from hospital. Conclusion : Patient with 4th Stadium of HIV AIDS required comprehensive and multidiciplinary management to improve their health condition.